AUDIT OF INCIDENTAL PINEAL CYSTS INVESTIGATION IN A DISTRICT GENERAL HOSPITAL. Issue 12 (15th November 2016) - AlMasri, Omar; Russell, Emily; O'Brien, Catherine; Dharia, Sonali; Smith, Gareth; Stewart, Jonathan; McLean, Brendan
Abstract : Incidental pineal cysts can be seen in up to 10.8% of patients undergoing brain imaging for unrelated reasons. The natural history is that of no change over several years while rarely there is a risk of an underlying malignant tumour. Atypical cysts do not necessarily correlate with risk of malignancy. As yet a national agreement on the management of these remains deficient and local guidelines are varied. We present our experience at a district general hospital of pineal cysts incidentally discovered on brain imaging. The workup follows the local Southwest of England guidelines for investigation and management of these cysts. Patients with atypical cysts undergo blood beta Human Chorionic Gonadotropin (b-HCG) and alpha Fetoprotein (AFP) sampling. If normal they undergo lumbar puncture (LP) for CSF b-HCG and AFP assessment. These are discussed in a regional neuro-oncology meeting. The audit spanned 1 year until July 2015. 48 patients were identified with incidental pineal cysts of which 11 were reported as atypical and underwent LP. None underwent intervention and imaging follow up intervals were variable between cases. We conclude that some patients underwent unnecessary invasive investigation (LP) and that there is a need to review the local guidelines or establish national guidance.